High-temperature superconductivity at high pressures for H3SixP1−x, H3PxS1−x, and H3ClxS1−x. (December 2016) - Fan, F.; Papaconstantopoulos, D.A.; Mehl, M.J.; Klein, B.M.
Abstract: Recent experimental and computational works have established the occurrence of superconducting temperatures, T c, near 200 K when the pressure is close to 200 GPa in hydrogen-based sulfur compounds. In this work we investigate the effects of phosphorus and chlorine substitutions of sulfur on T c, as well as the effect of hydrogen vacancies. In addition, we explore the superconductivity-relevant parameters in the H3 Si x P 1 − x system. In executing this work we used the virtual crystal approximation and performed a systematic set of linearized augmented plane wave calculations (LAPW) for many different concentrations of the sulfur component. From the densities of states and the scattering phase shifts at the Fermi level, we calculated electron-ion matrix elements and estimated the electron-phonon coupling constants for different concentrations, as well as T c . We find that the highest value of T c =197 K corresponds to a phosphorus concentration of x =0.15, or 8.85 valence electrons in a H3 P 0.15 S 0.85 alloy. From a detailed analysis of the results given by a Gaspari–Gyorffy (GG) determination of the Hopfield parameter, we identify the role of each term in the GG equation that produce the maximum T c . In addition, we present a non-orthogonal tight-binding parameterization of the band structure of H3 S which fits very well with the LAPW results. Abstract : Highlights: Substitution of Phosphorus for Sulfur in H3 S changes the transition temperature. Maximum superconducting temperature achieved for H3 P(0.15) S(0.85) . We determine each term in the Gaspari–Gyorffy equation for the Hopfield parameter. A non-orthogonal tight-binding parametrization reproduces first-principles results.